Associations of Mitochondrial Deoxyribonucleic Acid Polymorphisms With Behçet’s Disease in the Korean Population - Mihye KWON; Su-jin YOO; In Seol YOO; Jinhyun KIM; Seong Wook KANG; In Ah CHOI; Mi-kyoung LIM; Chung-il JOUNG (Archives of Rheumatology, 2019)
Objectives: This study aims to examine the possible associations of mitochondrial single nucleotide polymorphisms (SNPs) and Behçet’s disease (BD) in a larger patient group. Patients and methods: Whole blood or buffy coat was collected from 98 BD patients (31 males, 67 females; mean age 48±2.8 years; range 20 to 60 years) from four university hospitals located in the Chung-Cheong district of the Republic of Korea, and 196 age- and sex-matched healthy controls (HCs) (62 males, 134 females; mean age 46.91±12.90 years; range 20 to 68 years) from Konyang University Hospital. Twenty targeted mitochondrial deoxyribonucleic acids (DNAs) were genotyped and compared using the revised Cambridge Reference Sequence. Chi square and Fisher’s exact tests were used to analyze association of mitochondrial DNA SNPs with BD susceptibility and its clinical characteristics. Results: There were no differences for m.248A>G, m.304C>A, m.709G>A, m.3010G>A, m.3970C>T, m.4883C>T, m.5178C>A, m.6392T>C, m.6962G>A, m.10310G>A, m.10609T>C, m.12406G>A, m.12882C>T, m.13928G>C, m.14668C>T, m.16129G>A, and m16304T> between patient and HC groups. However, m.16182A>C and m.16183A>C were more frequently observed in the patient group than the HC group (22 [22.4%] vs. 24 [12.2%], p=0.061 and 32 [32.7%] vs. 42 [21.4%], p=0.092) but without statistical significance. m.4883C>T and m.5178C>A were associated with posterior location of oral ulcers (p=0.025 for each) and m.16183A>C was associated with deep oral ulcers (p=0.001), while m.16189T>C was associated with deep oral ulcers and thrombosis (p=0.042, 0.048, respectively). Conclusion: m.16182A>C and m.16183A>C may be associated with BD in the Korean population.